Evaluasi Tebal Lapis Tambah (Overlay) dengan Metode AASHTO 1993 dengan Data FWD - M H Gultom; R Gunawan; V Gustiawan (Jurnal MESIL (Mesin Elektro Sipil), 2024)
Analysis of the condition of the pavement structure with deflection data from the FWD (Falling Weight Deflectometer) measurement tool is to evaluate the strength of the installed pavement structure which is non-destructive (non-destructive test). The purpose of this study was to evaluate the thickness of the extra layer of flexible pavement using the Method AASHTO 1993 in the case study of the Binjai Outer Ring Road section. Using the planned ESAL from 2021 to 2031 of 22.985.580 on the Binjai Outer Ring Road section, the Method AASHTO 1993 which produces an overlay on the Binjai Ring Road section of 9,92 cm. in the alalysis of structural condition, FWD (Falling Weight Deflectometer) deflection data is used to calculate several variables in the Method AASHTO 1993, namely: the value of the Resilience Modulus of subgrade (MR), the value of the Effective Modulus above the subgrade (EP). Then the calculation is continued by using the pavement table data and PSI values to get the Structural Number Original (SNO), actual cumulative ESAL. Stuctural Number Effective (SNeff), pavement remaining life and Structural Number in Future (SNf). Assuming the thickness of the pavement layer affects the value of Elasticity Modulus during the back calculation process. This result also determines the value of the Elasticity Modulus taken at a distance thet meets the requirements of r ? 0,7 a_e which will affect the values of (SNeff) and (SNf) which are then used to determine the thickness of the overlay.